PENGARUH EFIKASI DIRI TERHADAP KETERLIBATAN SISWA PADA PEMBELAJARAN MATEMATIKA DI SMP NEGERI 03 KOTA JAMBI - Afdhol, Rahmi Syarima; Mukminin, Amirul; Rahmah Ramadhoni, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of student engagement in mathematics learning at SMP Negeri 03 Kota Jambi. The problem was indicated by students’ limited participation during classroom activities, low motivation in learning, and relatively poor academic achievement. Self-efficacy, defined as students’ belief in their ability to complete academic tasks, was considered an important factor influencing student engagement in learning activities. Therefore, this study aimed to identify students’ levels of self-efficacy, determine the level of student engagement, and examine the effect of self-efficacy on student engagement in mathematics learning. This research applied a quantitative approach using an ex post facto method. The population consisted of 315 students from grades VII, VIII, and IX, while the sample included 176 students selected through simple random sampling using the Slovin formula. Data were collected using Likert-scale questionnaires that had been tested for validity and reliability. The Cronbach’s Alpha coefficients were 0.712 for self-efficacy and 0.760 for student engagement. Data analysis techniques included descriptive statistics and simple linear regression analysis. The findings revealed that students’ self-efficacy was categorized as good, with an average score of 57.5. The regression analysis showed that self-efficacy had a positive and significant effect on student engagement, with a significance value of 0.000 and a regression coefficient of 0.553. These findings indicate that higher self-efficacy contributes to greater student engagement in mathematics learning activities. The results are expected to help schools design effective guidance programs that improve students’ confidence, participation, motivation, and involvement in mathematics learning more effectively.